Implementasi Pembelajaran STEM Low Cost di Sekolah Dasar untuk Mengembangkan Keterampilan Abad 21 - Kumala, Shifni Afida; Sa'dijah, Cholis; Hadi, Syamsul (University of Muhammadiyah Malang, 2023)
Students in the 21st-century era must have many skills. There needs to be learning that supports an independent curriculum and project-based learning. Meanwhile, schools still carry out their learning activities using the lecture method, which is less meaningful and has yet to explore students' abilities fully. STEM is a skill and knowledge acquired simultaneously by students. The aims of this study are that researchers want to obtain deeper information about 1) the background of STEM-based learning at SDI Aisyiyah, 2) the implementation of STEM-based learning at SDI Aisyiyah, and 3) the skills students acquire during STEM-based learning at SDI Aisyiyah. Researchers want to obtain more in-depth information about the background of learning in the school, the application of STEM learning in the school, and the skills that can be formed from STEM-based learning. This research uses a qualitative method whose data processing uses NVivo12. Nvivo 12 is the latest version of the application for processing qualitative research data. The research findings support 21st-century learning, project learning during a pandemic, implementing an independent curriculum, providing STEM training, creating fun learning and creating a low-cost STEM culture. STEM learning is held once a week. The syntax in STEM learning at SDI Aisyiyah is as follows: 1. The teacher selects and breaks down KD/TP in learning, 2. Giving triggering questions or problems, 3. Finding solutions or problem-solving by teachers and students, 4. Product design, 5. Product presentation or presentation, 6. Product correction and evaluation, and the last is product revision. Some of the skills that can be formed from STEM learning at SDI Aisyiyah are being able to work together, being able to think complexly, having an artistic spirit, being a more communicative, more creative child, being independent, etc.